2015
DOI: 10.1097/aap.0000000000000280
|View full text |Cite
|
Sign up to set email alerts
|

The European Society of Regional Anaesthesia and Pain Therapy and the American Society of Regional Anesthesia and Pain Medicine Joint Committee Practice Advisory on Controversial Topics in Pediatric Regional Anesthesia

Abstract: High-level evidence is not yet available for the topics evaluated, and most recommendations are based on Evidence B studies. The ESRA/ASRA recommendations intend to provide guidance for the safe practice of regional anesthesia in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 151 publications
(54 citation statements)
references
References 75 publications
(57 reference statements)
1
49
0
4
Order By: Relevance
“…1 Representatives from both ASRA and ESRA composed the joint committee practice advisory on LA dosage and adjuvants in PRA. Committee members met in work groups, and decisions on specific topics to be addressed were made through consensus.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Representatives from both ASRA and ESRA composed the joint committee practice advisory on LA dosage and adjuvants in PRA. Committee members met in work groups, and decisions on specific topics to be addressed were made through consensus.…”
Section: Methodsmentioning
confidence: 99%
“…The scientific evidence was classified according to the quality of research design as presented in Table 1, similar to what has been previously described in other practice advisories. 1 When the literature search revealed a lack of published studies or when the only evidence was generated from studies with insufficient quality due to methodological constraints, it was deemed as "insufficient literature," and expert opinion from the ASRA/ESRA joint committee was considered.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, lower extremity nerve blocks should only be performed with extreme caution if the patient has a concomitant neuraxial block. In contrast, both the ASRA and the European Society of Regional Anesthesia and Pain Therapy support the performance of nerve blocks under general anesthesia in pediatric patients,293 as multi-institutional prospective studies have demonstrated the safety of peripheral nerve blocks in children who are asleep 294–297…”
Section: Complications Of Lower Extremity Nerve Blocksmentioning
confidence: 99%
“…Of note, ASRA recommendations on this topic are different for pediatric patients. 8 The ASRA practice advisory and guideline processes are intended to provide learned recommendations, but not to replace common sense or sound clinical judgment. Scientific evidence is absent or conflicting with regard to regional blocks in asleep versus awake patients, and future evidence is not likely to emerge because serious longterm anesthesia-related perioperative nerve injury is so infrequent as to logistically preclude randomized controlled trials.…”
Section: Asleep Versus Awake and Standard Of Carementioning
confidence: 99%